Investing in resilience: A guide to climate risks and opportunities in Ethiopia’s key agricultural value chains. Report summary - ImpactSF; Tetratech; Centro Agronómico Tropical de Investigación y Enseñanza (CATIE); Mercy Corps Agrifin; Ethiopian Agricultural Tranformation Agency (ATI); Ministry of Agriculture (Ethiopia); Bioversity International and International Center of Tropical Agriculture; Gates Foundation (2025)
This report summarizes the results of the complete Clim-ARM project investment blueprint report (see link below) which analyses risk management solutions and investment opportunities across eight agricultural value chains in Ethiopia. The summary provides a call to action for three categories of stakeholders, each of which have their own investor brief in the series: 1. Clim-ARM project investment blueprint report: hdl.handle.net/10568/173562 2. Investor brief for providers of concessional capital: hdl.handle.net/10568/177046 3. Investor brief for providers of commercial capital hdl.handle.net/10568/177045 4. Investor brief for policymakers hdl.handle.net/10568/177047